Development of diagnostic assays for rapid and sensitive detection of Phytophthora infecting major spices and plantation crops - C N Biju, S Sasi, R T P Pandian, A I Bhat (Journal of Spices and Aromatic Crops, 2019)
Phytophthora, the ubiquitous stramenopile phytopathogen is a major threat to several economically important horticultural crops including spices and plantation crops. Trans-seasonal survival of Phytophthora in plant debris and soil continuum has considerable epidemiological significance as the quiescent propagules often serve as primary foci of infection with inherent potential to trigger epiphytotics in the succeeding season favoured by conducive environmental conditions. Hence, early and rapid detection of over summering propagules is highly imperative to manage Phytophthora induced diseases efficiently and economically. Twelve isolates representing different species of Phytophthora (P. capsici, P. tropicalis, P. palmivora. P. citrophthora and P. meadii) representing hosts such as black pepper, cardamom, nutmeg, coconut, arecanut and cocoa were used to develop nucleic acid-based diagnostic tools viz., polymerase chain reaction (PCR), real-time PCR, loop-mediated isothermal amplification (LAMP) and real-time LAMP. Phytophthora genus-specific primers were designed from the conserved region of nuclear ribosomal DNA. Each of the assays was specific and detected different species of Phytophthora and not other pathogens (Rhizoctonia solani, Pythium vexans, Fusarium oxysporum and Colletotrichum gloeosporioides) and plant samples. Sensitivity assays indicated that, real-time PCR detected Phytophthora upto 1.3 fg, followed by LAMP (13 fg) and PCR (13 pg).